2017
DOI: 10.1111/tri.13067
|View full text |Cite
|
Sign up to set email alerts
|

Using omics to explore complications of kidney transplantation

Abstract: SUMMARYThe importance of genetic and biochemical variation in renal transplant outcomes has been clear since the discovery of the HLA in the 1950s. Since that time, there have been huge advancements in both transplantation and omics. In recent years, there has seen an increased number of genome-, proteome-and transcriptome-wide studies in the field of transplantation moving away from the earlier candidate gene/protein approaches. These areas have the potential to lead to the development of personalized treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 105 publications
0
18
0
Order By: Relevance
“…GWASs have been applied to numerous hematologic endpoints and have advanced our knowledge of the genetic underpinnings of modifiers of complete blood count, hematopoiesis, cardiovascular diseases, and sickle cell anemia . Transplant research has benefitted from GWASs by identifying novel genes and alleles that are associated with kidney transplant rejection and clinical outcomes in patients with renal and lung transplants . Although advances in whole genome sequencing have made it possible to interrogate causal variants directly as opposed to evaluating variants that are in linkage disequilibrium with causal variants, array‐based genotyping remains a cost‐effective method for genotyping large cohorts, such as the UK Biobank cohort, in which half a million participants have been enrolled and genotyped .…”
mentioning
confidence: 99%
“…GWASs have been applied to numerous hematologic endpoints and have advanced our knowledge of the genetic underpinnings of modifiers of complete blood count, hematopoiesis, cardiovascular diseases, and sickle cell anemia . Transplant research has benefitted from GWASs by identifying novel genes and alleles that are associated with kidney transplant rejection and clinical outcomes in patients with renal and lung transplants . Although advances in whole genome sequencing have made it possible to interrogate causal variants directly as opposed to evaluating variants that are in linkage disequilibrium with causal variants, array‐based genotyping remains a cost‐effective method for genotyping large cohorts, such as the UK Biobank cohort, in which half a million participants have been enrolled and genotyped .…”
mentioning
confidence: 99%
“…There have been a few studies attempting to associate genetic variants with NODAT after kidney transplantation. [33][34][35] There have been reports that variants in the peroxisome proliferator-activated receptor α (PPARα) and P450 oxidoreductase (POR) genes are associated with increased risk for NODAT, but other studies do not validate these associations. 36,37 A recent case control study evaluating variants in kidney transplant recipients identified variants in the voltage-gated K+ channel (KCNQ1) gene, matrix metalloproteinase-2 (MMP2) gene and the glutathione peroxidans (GPX1) gene along with clinical factors have been reported to be associated with NODAT risk.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a handful of solid organ transplant GWA studies have been performed in modest numbers of patients and have focused mostly on renal transplantation (reviewed in an accompanying review article in this edition ) with very few significant findings. The only GWA study using heart transplant subjects was performed in relation to skin cancer outcomes .…”
Section: Genetics and Genome‐wide Studies In Heart Transplantationmentioning
confidence: 99%